Rare bird documentation form for Tundra Swan at Spirit Lake, 1998 - Harr, Douglas C.et al (1998)
Rare bird documentation form for four Tundra Swans at Spirit Lake in Dickinson County, IA on December 19, 1998. Epson - sheet feed